Waffles / Kristiane Müller-Urban - Müller-Urban, Kristiane
Covers the special characteristics of various waffle irons and provides tips and tricks relating to waffles. This title includes crisp Cinnamon Waffles, elegant Lemon Waffles, and Chimney Sweeps with Chocolate Cream.